Idosos da agricultura familiar na transição agroecológica no entorno da Floresta Nacional (FLONA) de Ipanema, Iperó –São Paulo - Dellai, William (2021)
This research analyzes the motivations and particularities of the participation of elderly family farmers in the agroecological transition process. The field research was carried out during the month of May 2020 with five (5) rural elderly people in two Agrarian Reform Settlements in the municipality of Iperó, state of São Paulo, and with one (1) elderly person (urban experience) in Araçoiaba da Serra - SP. These municipalities are covered by the National Forest Buffer Zone (FLONA) of Ipanema, a Federal Conservation Unit administered by ICMBio, which raises the importance of agroecological transition experiences in their surroundings. Through a qualitative approach using semi-structured interviews, the research addresses the involvement of the elderly in new networks of social relationships developed during the agroecological transition process and analyzes, through six (6) hypotheses, the role they play to strengthen and scale the agroecology in this territory. The agroecological transition is a dynamic and multifaceted process in which the elderly are inserted considering elements and challenges of the daily scenario and aspirations sought in the past through the activation of affective memory.